Las Tecnologías de información y comunicación en el proceso de enseñanza de la Matemática en el cuarto grado de Educación General Básica de la Unidad Educativa Marco Aurelio Subía Martínez – Batalla de Panupali”, 2021-2022. - Bustillos Cajas, Liliana Elizabeth (2022)
The present research work refers to the use of information and communication technologies linked to the process of teaching mathematics, emphasising that there is still limited updating in the methodologies for imparting knowledge, in addition to the fact that there is a notorious lack of interest and motivation on the part of the students, In this sense, the objective was to evaluate the effectiveness of the use of information and communication technologies in the process of teaching Mathematics to fourth year students of the Educational Unit "Marco Aurelio Subía Martínez - Batalla de Panupali", in the canton of Latacunga, in addition this study was guided by a qualitative-quantitative approach methodology; through which a systematised perspective of the study problem was acquired. The techniques used for this research were the survey with its respective questionnaire instrument and Observation with its guiding instrument Observation, with its guiding instrument of questions. The main results found refer to the fact that ICT in the teaching of mathematics can improve traditional teaching methods, providing a solution to a current educational problem, and can also be easily adaptable not only to virtual teaching processes but also to face-to-face processes, as interactive activities are included from the use of digital tools that are appropriate to the age and requirements in learning skills in the area of mathematics